Penilaian Kinerja Guru IPA Profesional (Studi Kasus pada SMP di Kabupaten Aceh Besar) - Juli Firmansyah; Dian Aswita (Jurnal Penelitian Pendidikan IPA, 2019)
Abstract: This study was aimed to analyze the performance of certified science teachers at SMP Negeri in Kabupaten Aceh Besar. The research consists of two stages, namely the stage of development of performance evaluation instruments and research phase of professional science teachers. The sample in this research is IPA teacher who served on 6 SMP in Kabupaten Aceh Besar. The performance evaluation instruments is developed through the FGD stage and refers to the assessment instrument used by the previous researcher. Data was collected by survey techniques. Data analysis using quantitative descriptive technique. The analysis results show that the performance of professional science teachers with high criteria of 40% and medium criteria of 60%. Implementation of learning done is good enough and has the maximum in preparing the lesson plans, create modules and learning media. The activeness of teachers in professional organizations in the field of education and social and academic achievement is still low. Not maximal efforts made in the development of his profession through the works produced, and also still less active in educational and training activities.Key Words: Evaluation; Science Teacher Performance; Certification